Legal analysis of the application of the principle of Contrarius Actus related to the cancellation of documents to fulfil citizen's right in population administration at the population and civil registration office - Tristiana, Enis; Wicaksono, Muhammad Bagus Adi; Mahardika, Alifia Putri; Kehwa, Napadol (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This research describes and examines the implementation of the Contrarius Actus principle in cancelling population documents and the obstacles to applying the Contrarius Actus principle in cancelling population documents. The type of research used is descriptive empirical research with a qualitative approach. The description of the research results is complemented by primary and literature data relevant to the research topic. The results of this study indicate that the application of cancelling population documents through the Contrarius Actus principle has its criteria, namely, not changing the meaning in population documents and population documents issued by the Population and Civil Registration Office. Based on the analysis of implementation theory by Merilee S. Grindle, implementing the Contrarius Actus principle in cancelling population documents follows and fulfils the indicators of the success of policy implementation, namely policy content and implementation environment. Although this implementation has gone well, some internal and external obstacles remain. Internal barriers include the absence of templates and detailed steps from the centre and the absence of Standard Operating Procedures (SOP) updates. External barriers include the high number of applications, the lack of understanding of this principle among the population, and the difficulty in determining the time between the applicant and the head of the field for the interview.